THE RELATIONSHIP BETWEEN INDIVIDUAL CHARACTERISTICS AND STRESS LEVELS WITH GASTRITIS INCIDENCE AMONG HIGH SCHOOL ADOLESCENTS: Hubungan Karakteristik Individu dan Tingkat Stres Terhadap Kejadian Gastritis Pada Remaja Sekolah Menengah Atas - Rosyidah, Aisyatur; Navika Yamani, Laura; Abdul Manas, Nor Hasmaliana (Jurnal Berkala Epidemiologi, 2026)
Background: Adolescents are at risk of developing gastritis due to their busy schedules, which often lead to poor eating habits and high stress levels. Gastritis has a high prevalence in Indonesia, particularly in the working area of the Alun-Alun Public Health Center in Gresik. Purpose: To analyze the relationship between individual characteristics and stress levels with the incidence of gastritis among high school adolescents in the working area of Alun-Alun Public Health Center, Gresik. Methods: Quantitative, analytical, observational, with a cross-sectional design, using a sample of 287 students, selected by proportionate stratified random sampling and simple random sampling. Data were collected through a questionnaire survey, including individual characteristics, DASS, and a recall of gastritis symptoms. The data were analyzed using univariate methods and chi-square tests to determine relationships among variables. Results: The results showed significant associations between age (p = 0.02; PR = 1.51; 95% CI = 1.08 < PR < 2.10), gender (p=0.01; PR = 2.03; 95% CI = 1.26 < PR < 3.26), history of pain reliever use (p=0.09; PR = 1.55; 95% CI = 0.94 < PR < 2.57), and stress levels (p<0.01) with the incidence of gastritis. The analysis of variables such as the history of medication use and mild, moderate, and extremely severe stress levels did not yield statistically significant results, making the estimated effects uncertain. Conclusion: Early adolescence, being female, and experiencing severe stress significantly increase the risk of developing gastritis.